An Examination of The Impacts of Macroeconomic Indicators on Conventional and Islamic Equity Fund Returns: Perspectives From The Mena Region - Elshabouny, Amr (AUC Knowledge Fountain, 2024)
This study examines the performance of conventional and Islamic equity mutual funds in the MENA region, and the influence of major macroeconomic determinants on the two types, by analyzing 503 conventional and 128 Shariah-compliant funds. It incorporates three major macroeconomic variables using Generalized Linear Models (GLM). The findings indicate no significant superiority of Islamic funds over conventional ones. The study also notes that while market performance and foreign exchange rates positively affect both fund types, GDP growth and inflation have a negative impact. Islamic funds are less influenced by excess market returns, GDP growth, and inflation compared to conventional funds, showing a distinct response to economic variables.